The Quandary of the Identity Debate (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Concepts of identity, identity formation, identity politics, and collective identity, despite being vague, are among the most used notions in social theory, historical analysis, and everyday life and politics. In the last four or five decades “identity” has become a catchword that could explain almost any political or cultural development. In this paper, I discuss existential and social dimensions of identity and identity formation, decode the relational and historical conditions of their construction and argue that identities at any given point of time represent a general (albeit multiple) and fragmented expression of human’s capacity. I further contend that identity is a social relation: an embodiment of power structures and power discourses. I end up with some reflections on how we can imagine communities compatible with human emancipation by replacing the particularity of identity with the universalism of humanity and focusing on humanity and discourses of human emancipation. This paper reconstructs the “identity debate” as a part of a conceptual deliberation of the narrative of historical change.
Keywords: Identity; Identity Formation; Identity Discourse; Power Relationship; Human Emancipation